2001
DOI: 10.1097/00003246-200101000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral autoregulation testing after aneurysmal subarachnoid hemorrhage: The phase relationship between arterial blood pressure and cerebral blood flow velocity

Abstract: CA can be assessed in a graded fashion in SAH patients. CA impairment precedes vasospasm; ongoing vasospasm worsens CA. CA assessment early after subarachnoid hemorrhage, within PHD 1-6, is predictive of outcome whereas late assessment is not. CA impairment is associated with cerebral vasospasm and low CPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 33 publications
6
105
0
Order By: Relevance
“…[17,18] The concept of impaired autoregulation mechanisms on admission in patients who later develop DCI has also been described in other articles. [4,7,9,13,15,19] This study also showed that CTP is a practical and useful tool to compare perfusion on admission and during follow-up in patients with SAH since in 87% of patients a good quality admission and follow-up scan was obtained and no side effects of the CT scanning with contrast occurred. Often, transcranial Doppler (TCD) monitoring is used for follow-up monitoring in patients with SAH for the presence of vasospasm.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…[17,18] The concept of impaired autoregulation mechanisms on admission in patients who later develop DCI has also been described in other articles. [4,7,9,13,15,19] This study also showed that CTP is a practical and useful tool to compare perfusion on admission and during follow-up in patients with SAH since in 87% of patients a good quality admission and follow-up scan was obtained and no side effects of the CT scanning with contrast occurred. Often, transcranial Doppler (TCD) monitoring is used for follow-up monitoring in patients with SAH for the presence of vasospasm.…”
Section: Discussionmentioning
confidence: 57%
“…In the hyperacute stage after SAH, intracranial pressure raises and cerebral perfusion pressure drops with consequently a decrease in CBF. [14,15] In the compensation for decreases further and the ability of vessels to dilate is exhausted, the CBF starts to decrease. The brain can compensate for this by increasing the extraction of oxygen from the blood.…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison of a CPP-or a ICP-oriented therapy, Robertson et al [39] showed a decrease in ischemic insult in CPP-oriented therapy, but an increase in respiratory complications with no convincing differences in outcome. There is agreement that body positioning may influence CPP and that it should be individualized for each patient based upon various data [13,25,41,47].…”
Section: Discussionmentioning
confidence: 99%
“…The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH. 3,35 In the present study, we have used an alternative index derived from systolic values of FV as previously described. 13,31,32 In one study of 32 patients with SAH changes in autoregulation during vasospasm were identified more accurately with Mx than with Sx.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…It has been described that cerebral autoregulation may become disturbed after subarachnoid hemorrhage (SAH), [1][2][3][4][5][6][7] which has been associated with development of delayed cerebral ischemia (DCI). 1,2,[5][6][7][8][9] The transient hyperemic response test (THRT) is a transcranial Doppler (TCD) based method, which characterizes the changes in cerebral blood flow velocity (FV) after a brief compression of the common carotid artery.…”
Section: Introductionmentioning
confidence: 99%